The impact of the psychological and social dimensions of digital transformation on the behavior of the individual and his family relations in the State of Kuwait - Alrashidi, Falah Saud Hasan (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to identify the psychological and social dimensions of digital transformation on the behavior of the individual and his family relationships, using the descriptive approach, on a sample of 245 participants, who were randomly selected, where they answered a questionnaire to identify the negative psychological and social effects of digital transformation on the individual and his family relationships (Prepared by the researcher), and the results indicated: There are statistically significant differences between males and females, in favor of males, in the negative impact of digital transformation on the level of individual behavior and social relations. The negative impact of digital transformation, in favor of the non-Kuwaiti, while there were no significant differences in the negative impact of digital transformation on the level of individual behavior and social relations due to the variables: age, educational level, and social status. The results also indicated that there were statistically significant differences between the negative impact of transformation. The digital transformation on individual behavior, and between the negative impact of digital transformation on social behavior, in favor of the negative impact of digital transformation on individual behavior. The study requires more studies to be conducted in this field.
Keywords: Digital transformation; psychological dimensions; social dimensions; individual behavior; family relationships